2018
DOI: 10.1093/abm/kax027
|View full text |Cite
|
Sign up to set email alerts
|

Sexual risk-taking and subcortical brain volume in adolescence

Abstract: These data highlight the potential relevance of subcortical socioemotional processing structures in adolescents' sexual decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 80 publications
1
6
0
Order By: Relevance
“…The current findings support sex differences in how substance use may interact with brain structure, which is well documented in the literature due to possible interactions with sex hormones during pubertal maturation (Feldstein Ewing et al, 2018;Gennatas et al, 2017). Preclinical research has shown that females may be particularly vulnerable to changes in neuronal structure and cognitive function with nicotine exposure during development (Cross, Linker, & Leslie, 2017), and adolescent neuroimaging studies have fairly consistently reported that females show greater negative associations between brain structure and alcohol use (Feldstein Ewing, Sakhardande, & Blakemore, 2014).…”
Section: Discussionsupporting
confidence: 83%
“…The current findings support sex differences in how substance use may interact with brain structure, which is well documented in the literature due to possible interactions with sex hormones during pubertal maturation (Feldstein Ewing et al, 2018;Gennatas et al, 2017). Preclinical research has shown that females may be particularly vulnerable to changes in neuronal structure and cognitive function with nicotine exposure during development (Cross, Linker, & Leslie, 2017), and adolescent neuroimaging studies have fairly consistently reported that females show greater negative associations between brain structure and alcohol use (Feldstein Ewing, Sakhardande, & Blakemore, 2014).…”
Section: Discussionsupporting
confidence: 83%
“…Even fewer studies have examined the role of puberty and brain development in adolescent health risking behaviors. Pubertal stage has been found to moderate the association between limbic brain structure and risky sexual behaviors (Feldstein Ewing et al, 2018), and greater testosterone levels has been associated with increased alcohol use in males via amygdala-OFC resting state connectivity (Peters et al, 2015). Interestingly, there has been no research to date on how puberty and brain development may together predict positive outcomes such as prosociality, normative sexual development and health promoting behaviors (see Suleiman et al, 2017).…”
Section: Overviewmentioning
confidence: 99%
“…High socioeconomic status (SES) (Oshri et al, 2019) protects children against antisocial behaviors (Palma-Coca et al, 2011), school problems (Sirin, 2005), learning disorders (Fluss et al, 2009), attention deficit and hyperactivity disorder (Assari & Caldwell, 2019a;Collins & Cleary, 2016;Jablonska et al, 2020;Machlin, McLaughlin, & Sheridan, 2019), aggression (Heshmat et al, 2016), early sexual initiation (Feldstein Ewing et al, 2018), and use of tobacco (Barreto, de Figueiredo, & Giatti, 2013;Kaleta, Usidame, Dziankowska-Zaborszczyk, & Makowiec-Dabrowska, 2015), alcohol (Moore & Littlecott, 2015;Silveira et al, 2014), and drugs (Gerra et al, 2020). The effects are partially attributed to the effects of SES on brain development (Javanbakht et al, 2015;Masten, Telzer, & Eisenberger, 2011;Wu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%